On the identity of Terpnosia graecina (DISTANT) and description of new species Terpnosia lamrii sp. nov. from Malaysia - Azman Sulaiman (Penerbit Universiti Kebangsaan Malaysia, 2023)
Terpnosia graecina (Distant) is re-examined and redescribed. This has lead to discovery of a new species Terpnosia lamrii sp. nov. and herewith described as new to science